Risk Assessment and the Impacts of Cultism Crisis in the Selected Communities in Gokana Local Government Area of Rivers State, Nigeria - Okwori Peter Benson; A. Obafemi Andrew; Asomaku Sunny Oghenefegor; Wali Elekwachi (Archives of Current Research International, 2022)
Cultism irrespective of several actions at lessening it, emanated from Nigeria’s communities. Cultism has projected despair over the peaceful and communal co-existence within our communities. It therefore became overbearing to thoroughly review the issue of cultism in our Communities where great moral values childhood should control over feeling. Without a doubt, the issue has expected sickening extent as cultic violence flourishes considerably more. The fundamental reason for this study is to evaluate the risk and the effect of cultism emergency in the selected Communities in Gokana Local Government Area of Rivers State Nigeria. The aim of this study is to assess the risk and the impact of cultism crisis in the selected Communities in Gokana Local Government Area of Rivers State Nigeria. Both primary and secondary data sources were employed in this study. A descriptive statistics such as simple bar chart in percentages was used through the Statistical Package for Social Sciences (SPSS) Version 20.2 and Microsoft Excel 2007 software to analyse the information generated. The instrument utilized were structured and closed ended questionnaire. Conclusively, we can say that there must be an improved facilities and improved living conditions in these selected communities so as to minimize perceived strain in the social system which underlines cultism crisis in the study area. The administrative authorities of these selected communities must show doggedness in their determination to stamp out cultism. They must brace up to the challenges of cultism, which has become one of the most potent evils of the recent time.